Facile and rapid fabrication of porous CuBr films by solution oxidation and their application for the exclusive detection of NH3 at room temperature. Issue 2 (20th December 2021) - Kim, Sang-Kwon; Yu, Byeong-Hun; Na, Chan Woong; Lee, Jong-Heun; Yoon, Ji-Wook
Abstract : A porous CuBr film with exclusive NH3 sensing properties is prepared via a simple solution process, which offers the best opportunity for realizing low-cost, wearable devices for indoor air quality monitoring. Abstract : Porous CuBr films are the most promising platform for the exclusive detection of NH3 but their simple and cost-effective fabrication without employing a high-temperature process remains elusive. Herein, we report the facile and low-temperature preparation of porous CuBr films by a solution oxidation method, and their unprecedentedly high NH3 sensing properties. The porous CuBr films are prepared by coating Cu thin films with different thicknesses (10–100 nm) on sensor substrates by direct current sputtering, immersion of Cu thin films in a CuBr2 solution (0.001–0.1 M) for a controlled time (10–300 s), and washing of the substrate with methanol. Among the CuBr film sensors, the sensor fabricated by immersing the 30 nm-thick Cu film in 0.01 M CuBr2 solution for 120 s (30n-120s sensor) exhibits the highest NH3 response (resistance ratio = 211), which is the highest level compared with those reported in the literature. Moreover, the 30n-120s sensor exhibits ultrahigh NH3 selectivity, extremely low detection limit (∼25 ppb), excellent reversibility, and long-term stability at room temperature. The sensing film of the 30n-120s sensor has a porous structure consisting of loosely percolated CuBr particles, whereas the other films have a dense structure with tightly percolated particles or, conversely, an island configuration composed of nearly discrete particles. The superior NH3 sensing properties of the sensor are discussed in terms of the porosity and particle connectivity of the film. The high performance NH3 sensor can be used to realize flexible and even wearable NH3 detectors for emerging applications such as environmental monitoring, food freshness assessment, and breath analysis for disease diagnosis.